The effect of using recycled concrete aggregates RCA as coarse aggregates on Hot mixed asphalt HMA properties - Abbas, samira (Latakia University Journal -Engineering Sciences Series, 2025)
The process of recycling construction wastes is considered one of the modern sustainable technology techniques with increasing interest around the world in order to develop integrated sustainable plans and solutions. That contributes positively in reducing the demand for natural resources in their actual conditions of rarity, in parallel with the increasing amounts of demolition wastes around the world due to the rapid urban growth, which become a serious threat to the environment. The aim of this study is to evaluate the faculty of using recycled aggregates from concrete demolition products (RCA) as a coarse aggregates, as an alternative to natural ones in hot asphalt mixtures (HMA), by using Marshall Method with different percentages of RCA, (0 – 25 – 50 - 75 – 100)%, and to describe their properties. The mixtures with coarse recycled aggregates results were in accordance with the required specification. Meanwhile, the replacement ratio up to 50% has shown an improvement in the performance compared to natural mixtures. However, replacement ratios above 50% have worsen the performance of the mixtures due to the low quality of RCA aggregates ,in addition to a noticeable increase in the optimal bitumen content Required for mixtures .